INEQUALITY, INCENTIVES, CRIMINALITY, AND BLAME. (8th May 2017) - Lewis, Christopher
ABSTRACT: The disadvantaged have incentives to commit crime, and to develop criminogenic dispositions, that limit the extent to which their co-citizens can blame them for breaking the law. This is true regardless of whether the causes of criminality are mainly "structural" or "cultural." We need not assume that society as a whole is unjust in order to accept this conclusion. And doing so would neither stigmatize nor otherwise disrespect the disadvantaged.